Pengaruh kepimpinan, lokus kawalan dan efikasi kendiri ke atas pematuhan perintah tetap Komisioner Jeneral Penjara di Jabatan Penjara Malaysia - Zulkifli, Omar (2014)
Compliance with standing orders among the officers and the staff of the Prison Department of Malaysia strongly correlated with leadership and gives great impact on work satisfaction and to reduce the cases of severe offenses that occur in the prison. However the research does not do an in-depth studies involving psychological factors such as leadership, locus of control and self-efficacy. This research conducted for the purpose of identifying the influence of the leadership, locus of control and self-efficacy towards the compliance with standing orders of the Prison Commissioner General of Prison Department of Malaysia. This research also examined the differences of compliance with standing orders, leadership, locus of control and self-efficacy by grade and gender differences. The researcher also would like to identify the most dominant factor affecting the compliance with standing orders. The study was carried on to the officers and members of the Prison Department of Malaysia in 30 prisons across Malaysia. The questionnaire used in this study includes Leadership Questionnaire by Maxwell(1998), Locus of Control Scale by Mueller and Thomas(2000) and The General Self-efficacy Scale (GSE) by Schwarzer and Matthias(2000). A total of 433 respondents consisting of officers and prison’s staffs were selected through stratified random sampling method. Data were analyzed using Pearson correlation-test and simple regression test. The results showed a significance relationship between difference leadership and compliance with standing orders. In addition, there was no relationship between the locus of control and self-efficacy with the standing orders. The results also indicated the differences in leadership, locus of control and self-efficacy according to grade, but for the compliance with standing orders regulation showed no differences. According to the gender, the result showed differences in external locus of control but, there were no differences in the compliance with standing orders regulation, leadership and self-efficacy. A regression test also showed that leadership and selfefficacy were the factors that influence the compliance with standing orders regulations. Therefore, leadership and self-efficacy are the main factors that influence the compliance with standing orders among the officers and the prison’s staffs. To enhance the excellence of the department, the Prison Department of Malaysia should focus on the leadership and self-efficacy training.